Harnessing the potential of human induced pluripotent stem cells, functional assays and machine learning for neurodevelopmental disorders - Ziqin Yang; Ziqin Yang; Nicole A. Teaney; Nicole A. Teaney; Elizabeth D. Buttermore; Elizabeth D. Buttermore; Elizabeth D. Buttermore; Mustafa Sahin; Mustafa Sahin; Mustafa Sahin; Wardiya Afshar-Saber; Wardiya Afshar-Saber (Frontiers in Neuroscience)
Neurodevelopmental disorders (NDDs) affect 4.7% of the global population and are associated with delays in brain development and a spectrum of impairments that can lead to lifelong disability and even mortality. Identification of biomarkers for accurate diagnosis and medications for effective treatment are lacking, in part due to the historical use of preclinical model systems that do not translate well to the clinic for neurological disorders, such as rodents and heterologous cell lines. Human-induced pluripotent stem cells (hiPSCs) are a promising in vitro system for modeling NDDs, providing opportunities to understand mechanisms driving NDDs in human neurons. Functional assays, including patch clamping, multielectrode array, and imaging-based assays, are popular tools employed with hiPSC disease models for disease investigation. Recent progress in machine learning (ML) algorithms also presents unprecedented opportunities to advance the NDD research process. In this review, we compare two-dimensional and three-dimensional hiPSC formats for disease modeling, discuss the applications of functional assays, and offer insights on incorporating ML into hiPSC-based NDD research and drug screening.